Effect of Head Position on Levator Veli Palatini Muscle Activity in Patients with Borderline Velopharynge al Competence/ Incompetenc e - HARA, Hisanaga; TACHIMURA, Takashi; WADA, Takeshi (Journal of Japanese Cleft Palate Association, 2000)
The purpose of this study was to evaluate the effect of head position on activity of the levator veli palatini muscle, the major muscle involved in velopharyngeal closure, during speech in speakers with borderline velopharyngeal competence / incompetence ( BVP ). Five speakers with BVP were studied. Smoothed EMGs of the levator veli palatini muscle were respectively recorded in three head positions: In the first ( Condition-1), the head was in the flexed position; in the second ( Condition-2), the head was in the upright position, and in the third ( Condition-3), the head was in the extended position. The subjects produced the speech sample [pu] 10 times in each condition. Levator veli palatini muscle activity was not significantly different between Condition-1 and Condition-2. However, activity in Condition-3was significantly greater (p<0.01; t-test) than in Condition-1 and Condition-2. The results of this study suggest that velopharyngeal function is influenced by a change in head position. That is, the extended position may require greater activity of the levator muscleto close the velopharynx adequately.